Evaluasi Kinerja Proyek Konstruksi Ditinjau dari Aspek Biaya dan Waktu Menggunakan Metode Earned Value Analysis, Studi Kasus: Pembangunan Gedung Perkantoran Balai Besar Wilayah Sungai (BBWS) Bengawan Solo - Rasa, Barem Talang; Handayani, Krisna Dwi (Portal: Jurnal Teknik Sipil, 2023)
The growth of Indonesia's population has an impact on increasing infrastructure needs to support economic activity. Construction projects have to be done in order to meet those needs. It is certain that in its implementation there are many potential deviations. Project planning, control, and evaluation have to be done as an effort to improve project performance. Earned Value Analysis (EVA) method is a tool that has an ability to evaluate project performance in terms of cost and schedule aspects. The BBWS Bengawan Solo Office Building Construction Project was a government project intended to improved the quality of public services. The implementation of the EVA method on the project was done with the aim of evaluating cost and time performance. EVA carried out up to the 20th reporting period, obtained a CV value of IDR 2,238,617,582.39 and an SV value of IDR 5,939,213,594.86, while the CPI value was 1,251 and the SPI value was 2,437. The project's performance in the cost and schedule aspects was considered good, so it was estimated that the project could be completed 90 days faster with a profit of IDR 4,493,629,178.46.